Assessment of level and source of stress in mothers of newborns admitted to neonatal intensive care unit in tertiary care hospital - Basamma; Patil, Basavaraj M.; Meenakshi, Nayanatalli; Itagi, Rudrakshi (International Journal of Contemporary Pediatrics, 2024)
Background: The hospitalization of a neonate is stressful for the mother and all family members Severe stress can affect mother–baby relationship and thus affect newborn development subsequently. The parent-infant bonding process during the newborn period establishes the foundation a lifelong relationship. This process is affected when the newborn spends the first several weeks in NICU. Quantifying stress levels of parents and identifying environmental stressor is useful in assisting the health personnel in improving the quality of medical care. To study the level and source of stress in mothers of Newborns admitted in the Neonatal intensive care unit and to quantify the stress levels by parental stressor scale. Methods: In this cross-sectional study included 400 mothers of newborn babies admitted in NICU of Basaveshwar Hospital and Sangameshwar hospital attached to Mahadevappa Rampure Medical College, Kalaburgi with semi structured validated interview-based questionnaire consisting of parenteral stressor scale: NICU (PSS: NICU) comprising three subscales and questions related to maternal and neonatal characteristics will be used. Results: Among the study population the mean stress score was maximum in parental role domain of PSS: NICU stress scale. The maternal stress was higher among preterm and non-breast-fed babies in looks and behaviour and parental role. Maternal stress was statistically significant among rural, illiterate and home maker participants in all 3 domains. Conclusions: NICU mothers are under significant stress and appropriate counselling targeted towards specific stressors is required and before designing remediation programs for parents, local demography and the predominant NICU stressors need to be kept in mind. maternal stress, neonatal intensive care unit environment, baby looks and behaves.